PSYCHOEDUCATION GET OUR FUTURE: OPTIMIZING THE ROLE OF PARENTING EDUCATION IN IMPROVING MENTAL HEALTH LITERACY OF CHILDREN WITH DISABILITIES - Yudowati, Kristin Afriyani; Suwari, Suwari (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This study aims to optimize the role of parenting education in improving mental health literacy of children with disabilities. Through the psychoeducation program "Get Our Future", it is hoped that every individual, both parents, educators, and expert professionals, can better understand the condition of children. Recognize signs of mental disorders, and be able to provide appropriate support. The research method used is to use the library research method and integrate psychoeducational methods, where in this study it is hoped that it can provide a significant understanding of the learning process and behavior changes that occur in the context of parenting education and be able to develop effective intervention programs to support the mental health of children, parents, educators and professional experts. parenting and being able to develop effective intervention programs to support the mental health of children, parents, educators and professional experts. Psychoeducation programs can be carried out directly or indirectly. From the results of literature review and psychoeducational methods where this study has shown that there are changes after the program is designed. Then, from these results, there will be a significant increase in the child's knowledge of mental disorders, communication and emotional skills, and his confidence level. Not only that, this psychoeducation program also has a positive impact on children's behavior, such as decreasing anxiety levels and increasing adaptability. In conclusion, the program designed through the "Get Our Future" program is an effective intervention in parenting education to improve mental health literacy of children with disabilities. Not only that, Not only that, the results of this study will also show how important it is to integrate the Get Our Future psychoeducation method of parenting education into the education system so that it can develop through information technology that is more flexible and affordable Then, this research has also suggested the development of similar programs that can be accessed by more readers.